Central America Community-Based Approaches to IPV : The Case for Community Mobilization Interventions to Prevent Intimate Partner Violence - World Bank (Washington, DC, 2016)
This review focuses specifically on Intimate partner violence (IPV) against women, as opposed to Violence against women and girls (VAWG) more broadly, for several reasons. Partner violence is the most prevalent form of violence against women globally: a woman is at the greatest risk for suffering violence in her own home by someone she knows. A recent systematic review found that most of effective evaluations and programs on VAWG have been directed to IPV. This paper emphasizes results of these and other primary prevention programs, not because secondary and tertiary prevention programs are ineffective, but because primary prevention programs allow for macro-level programming that targets root causes of violence, such as harmful gender norms, to create generations of men, women, boys, and girls who not only no longer accept violence, but also feel empowered to eliminate it. To conclude, this methodological annex outlines the steps involved in adapting to new settings a community-based intervention to prevent intimate partner violence. While the precise nature of these steps will vary depending on the setting in which they are applied, the core ethical and effectiveness considerations here should remain true regardless of location. The authors hope that this note will help programmers worldwide to successfully transform community norms and prevent intimate partner violence.